5VA high-flame-retardancy ABS (acrylonitrile-butadiene-styrene) resin composition and preparation method thereof
By using tetravitromer-A carbonate polymer and nanomoniated soil coordinating charcoal in ABS resin, and combined with low molecular weight surface active agents to improve the decentralization of nanomonly losing ground, solve the existing ABS resin flame retardant retardant The problem of low flame retardant efficiency and poor physical properties in technology have realized the dual improvement of 5VA high flame retardant performance and physical properties.
Patent Information
- Application Number
- CN202411589435.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-24
AI Technical Summary
The existing ABS resin flame retardant technology has defects such as low flame retardant efficiency, large amount of inorganic substances and bromine-antimony flame retardant, and poor physical properties of flame retardant ABS, making it difficult to meet the higher flame retardant standards of 5VA, especially in thin walls. In the material.
By using tetrabroma-A carbonate alfalty pool and nanomon to get rid of soil coordinating charcoal, it significantly enhances the carbon formation capacity of ABS resin, combined with low-molecular weight surface active agents to improve the decentralization of nanomonia soil and the peeling effect of the layer layer. , Reduce the amount of inorganic fillers and bromine and crickets.
The dual improvement of the 5VA high flame retardant performance and physical properties of ABS resin can meet the stricter flame retardant standards, such as IEC62368 S.2, which reduces the overall filler added and improves liquidity.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a flame retardant ABS resin composition, in particular to a 5VA highly flame retardant ABS resin composition and a preparation method thereof. Background Art
[0002] Acrylonitrile-butadiene-styrene copolymer resin (ABS resin) is an engineering plastic widely used in various fields. It has excellent physical properties such as high impact strength, heat resistance, low temperature resistance, and chemical corrosion resistance. It also has excellent processing performance, appearance, and dimensional stability. It plays an indispensable role in many industries such as electronics, new energy batteries, automobile manufacturing, home appliances, and office equipment.
[0003] ABS resin is a flammable polymer material with an oxygen index of only 18.3-20. Therefore, in applications involving electrical and battery applications, ABS resin usually needs to be modified by adding flame retardants to meet strict safety and fire protection standards. At present, the commonly used flame retardant systems for ABS resin include a synergistic system of brominated flame retardants and antimony trioxide. This combination can give ABS stable flame retardant properties while maintaining relatively excellent mechanical properties.
[0004] Although the bromine-antimony flame retardant system can effectively improve the flame retardancy of ABS resin through the gas phase flame retardant mechanism to achieve a V-0 flame retardant grade, the flame retardant ABS resin on the market usually cannot meet the higher flame retardant standard of 5VA because the system and ABS resin itself do not have good carbonization ability; especially for thin-walled materials with a thickness of 2.0 mm or less, it is even more challenging to achieve a 5VA level of flame retardant performance. In order to improve this problem, a common practice is to add a large amount of inorganic fillers, but this often significantly reduces the physical properties of the flame retardant ABS resin.
[0005] Patent CN109627671B provides an ABS composite material, which contains the following components in parts by weight: 34 to 78 parts of ABS resin, 3 to 20 parts of SAN resin, 1 to 10 parts of toughening agent, 12 to 20 parts of flame retardant, 3 to 6 parts of flame retardant synergist, 3 to 15 parts of inorganic filler, 0.1 to 0.5 parts of anti-dripping agent and 0 to 2 parts of auxiliary agent; the composite material has a high flame retardant grade, good comprehensive performance, and achieves a balance between strength and notched impact performance. Patent CN101787174B provides a flame-retardant ABS modified resin with a low L value (less than 27) and a preparation method thereof, wherein the resin comprises the following components and contents (parts by weight): ABS resin 100, bromine flame retardant 10-25, inorganic flame retardant masterbatch 20-40, anti-dripping agent 0.1-0.5, antioxidant 0.2-1, light stabilizer 0.1-0.5, lubricant 1-3 and black masterbatch 1-4; the disadvantage of the existing flame-retardant ABS resin with a high L value (i.e., low blackness) is overcome, and a new and efficient flame-retardant compound synergistic technology is adopted, by reasonably selecting the particle size of antimony trioxide, carbon black lubricating dispersion system, and masterbatch processing technology, while maintaining the original excellent performance of the flame-retardant ABS resin, giving the resin a higher blackness. However, the main point of the invention of this patent is to solve the problem of poor dyeing of flame-retardant ABS, especially the problem of not being able to dye black, rather than improving its thin-wall flame-retardant performance.
[0006] In summary, the existing ABS resin flame retardant technology has the defects of low flame retardant efficiency, large amount of inorganic and bromine-antimony flame retardant added, and poor physical properties of flame retardant ABS. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a 5VA high flame retardant ABS resin composition and a preparation method thereof, which reduces the content of inorganic fillers and bromine and antimony, significantly improves the flame retardant properties of the ABS resin, and improves the physical properties of the ABS resin.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] The present invention provides a 5VA high flame retardant ABS resin composition, which comprises the following components in parts by weight:
[0010]
[0011] Furthermore, the ABS resin is selected from any one of acrylonitrile-butadiene-styrene copolymer (ABS resin), acrylonitrile-butadiene-acrylate copolymer, methyl methacrylate-butadiene-styrene copolymer or acrylonitrile-ethylene propylene diene monomer rubber-styrene copolymer.
[0012] Furthermore, the chlorine content of the chlorinated polyethylene is 32% to 35%. If the chlorine content is higher than 35%, the toughening effect and thermal stability are poor. If the chlorine content is lower than 32%, its flame retardant properties will be affected.
[0013] Furthermore, the aromatic brominated flame retardant is selected from at least one of 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer, decabromodiphenylethane, brominated epoxy resin or brominated polystyrene.
[0014] Furthermore, the aromatic brominated flame retardant is preferably 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer.
[0015] Furthermore, the antimony-based flame retardant synergist is selected from any one of antimony trioxide, antimony pentoxide or sodium antimonate.
[0016] Furthermore, the nano carbon-forming masterbatch is a nano montmorillonite masterbatch, which comprises the following components by weight: 40 to 50 parts of acrylonitrile-butadiene-styrene copolymer (ABS resin), 45 to 60 parts of nano montmorillonite (MMT), 3 to 5 parts of surfactant and 0.5 to 1 part of processing aid.
[0017] Furthermore, the surfactant is a styrene-maleic anhydride copolymer (SMA) with a molecular weight of 5000 to 20000. If the molecular weight is higher than 20000, the surface wettability is poor, and the lamella peeling and dispersion of the nano-montmorillonite cannot be effectively improved, which ultimately affects the flame retardant effect; the content of maleic anhydride in the surfactant is 18wt%-25wt%; the processing aid is selected from at least one of hindered phenol antioxidants, phosphite antioxidants, thioester antioxidants, polyethylene wax, oxidized polyethylene wax, ethylene bis stearamide (EBS), pentaerythritol stearate (PETS), erucamide, silicone oil, magnesium stearate, and calcium stearate lubricants.
[0018] Furthermore, the preparation method of the nano carbon masterbatch comprises the following steps:
[0019] acrylonitrile-butadiene-styrene copolymer (ABS resin), nano-montmorillonite (MMT), surfactant and processing aid are sent into a high-speed mixer for stirring, and after being fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain nano-carbon masterbatch;
[0020] The twin-screw extruder has a screw length-to-diameter ratio of 30-50, and is equipped with a temperature control device and a vacuum pumping device. The extrusion temperature is 190° C. to 230° C., and the screw speed is 300 rpm to 500 rpm.
[0021] Furthermore, the anti-dripping agent is selected from polytetrafluoroethylene with a molecular weight of 3 million to 5 million, Any one of AD high-performance silicon-coated anti-drip agent, Flyho K-PT201 or Flyho K-PT107; the antioxidant is selected from at least one of Irganox 1010, Irganox 1076, Irganox B900 or Irganox 168; the light stabilizer is selected from at least one of 1-hydroxybenzotriazole, 2-hydroxybenzophenone, UVP, hindered amine light stabilizer 770 or salicylate; the lubricant is selected from at least one of ethylene bisstearamide (EBS), white oil, fatty acid amide, barium stearate, magnesium stearate, polyethylene wax, silicone oil, ethylene-vinyl acetate copolymer or ethylene-acrylic acid copolymer.
[0022] The present invention also provides a method for preparing any of the above 5VA highly flame-retardant ABS resin compositions, comprising the following steps:
[0023] ABS resin, chlorinated polyethylene, aromatic brominated flame retardant, antimony flame retardant synergist, nano carbon masterbatch, anti-dripping agent, antioxidant, light stabilizer and lubricant are fed into a high-speed mixer for stirring, and after being fully mixed in the high-speed mixer, they are fed into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screws, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a 5VA high flame retardant ABS resin composition;
[0024] The twin-screw extruder has a screw length-to-diameter ratio of 30-50, and is equipped with a temperature control device and a vacuum pumping device. The extrusion temperature is 200° C. to 240° C., and the screw speed is 300 rpm to 500 rpm.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention provides a 5VA highly flame-retardant ABS resin composition and a preparation method thereof. The composition has excellent performance and stable flame retardant effect, and in the preparation process, tetrabromobisphenol-A carbonate oligomer with strong carbon-forming ability and nano-montmorillonite are used to synergistically form carbon. This preparation method greatly improves the flame retardant efficiency, while reducing the use of inorganic fillers and bromine and antimony, thereby achieving a dual improvement in the flame retardant performance and physical properties of the ABS resin.
[0027] (2) The present invention provides a method for preparing a 5VA high flame retardant ABS resin composition. On the one hand, the preparation method of the present invention utilizes tetrabromobisphenol-A carbonate oligomer and nano-montmorillonite to synergistically form carbon, which significantly enhances the carbon forming ability of ABS resin during combustion and improves its flame burn-through resistance, thereby improving the flame retardancy level of 5VA; in addition, in order to further enhance the flame retardant effect of nano-montmorillonite, the present invention uses a low molecular weight surfactant styrene-maleic anhydride copolymer (SMA) to interact with the alkylated ammonium salt in the nano-montmorillonite (MMT), which not only improves the dispersibility of the nano-montmorillonite itself, but also makes the nano-montmorillonite layer peeling more thorough. The application of this flame retardant system greatly improves the overall flame retardant efficiency and makes it easier to obtain 5VA high flame retardancy. On the other hand, the preparation method of the present invention reduces the amount of inorganic matter and bromine-antimony flame retardant added, avoids the reduction of the physical properties of the flame retardant ABS resin caused by the addition of a large amount of inorganic fillers and flame retardants, and the physical properties of the flame retardant ABS resin are also improved. In summary, the preparation method of the present invention significantly improves the flame retardancy and physical properties of ABS resin, and can meet new flame retardancy standards such as IEC62368 S.2. Therefore, the 5VA high flame retardant ABS resin composition and the preparation method thereof of the present invention have broad application prospects.
[0028] (3) The key to the present invention is the use of low molecular weight surfactants, which can fully exfoliate and disperse the nano-montmorillonite. At the same time, the brominated PC (tetrabromobisphenol-A carbonate oligomer) that is easy to form carbon is used as a flame retardant to coordinate carbonization, thereby improving the efficiency of flame retardant carbonization, thereby greatly reducing the amount of overall filler added, reducing density, and improving fluidity. In addition, the amount of filler added in the present invention is less than 50% of that in patent CN109627671B. DETAILED DESCRIPTION
[0029] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0030] The present invention provides a 5VA high flame retardant ABS resin composition, which comprises the following components in parts by weight:
[0031]
[0032] The ABS resin is selected from any one of acrylonitrile-butadiene-styrene copolymer (ABS resin), acrylonitrile-butadiene-acrylate copolymer, methyl methacrylate-butadiene-styrene copolymer or acrylonitrile-ethylene propylene diene monomer rubber-styrene copolymer; the chlorine content of chlorinated polyethylene is 32% to 35%. If the chlorine content is higher than 35%, the toughening effect and thermal stability are poor. If the chlorine content is lower than 32%, its flame retardant performance will be affected; the aromatic brominated flame retardant is selected from at least one of 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer, decabromodiphenylethane, brominated epoxy resin or brominated polystyrene; the antimony-based flame retardant synergist is selected from any one of antimony trioxide, antimony pentoxide or sodium antimonate;
[0033] The nano carbon-forming masterbatch is a nano montmorillonite masterbatch, which comprises the following components by weight: 40 to 50 parts of acrylonitrile-butadiene-styrene copolymer (ABS resin), 45 to 60 parts of nano montmorillonite (MMT), 3 to 5 parts of surfactant and 0.5 to 1 part of processing aid. The surfactant is a styrene-maleic anhydride copolymer (SMA) with a molecular weight of 5000 to 20000. If the molecular weight is higher than 20000, the surface wettability is poor, and the lamella peeling and dispersion of the nano montmorillonite cannot be effectively improved, thereby ultimately affecting the flame retardant effect. The content of maleic anhydride in the surfactant is 18wt%-25wt%. The processing aid is selected from at least one of hindered phenol antioxidants, phosphite antioxidants, thioester antioxidants, polyethylene wax, oxidized polyethylene wax, ethylene bis stearamide (EBS), pentaerythritol stearate (PETS), erucamide, silicone oil, magnesium stearate, and calcium stearate lubricants. The preparation method of the above-mentioned nano-carbon masterbatch includes the following steps: sending acrylonitrile-butadiene-styrene copolymer (ABS resin), nano-montmorillonite (MMT), surfactant and processing aid into a high-speed mixer for stirring, stirring and mixing in the high-speed mixer, and then sending them into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain nano-carbon masterbatch; the twin-screw extruder has a screw aspect ratio of 30 to 50, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm to 500 rpm.
[0034] The anti-dripping agent is selected from polytetrafluoroethylene with a molecular weight of 3 million to 5 million, Any one of AD high-performance silicon-coated anti-drip agent, Flyho K-PT201 or Flyho K-PT107; the antioxidant is selected from at least one of Irganox 1010, Irganox 1076, Irganox B900 or Irganox 168; the light stabilizer is selected from at least one of 1-hydroxybenzotriazole, 2-hydroxybenzophenone, UVP, hindered amine light stabilizer 770 or salicylate; the lubricant is selected from at least one of ethylene bisstearamide (EBS), white oil, fatty acid amide, barium stearate, magnesium stearate, polyethylene wax, silicone oil, ethylene-vinyl acetate copolymer or ethylene-acrylic acid copolymer.
[0035] The above 5VA high flame retardant ABS resin composition is prepared by the following method:
[0036] ABS resin, chlorinated polyethylene, aromatic brominated flame retardant, antimony flame retardant synergist, nano carbon masterbatch, anti-dripping agent, antioxidant, light stabilizer and lubricant are sent into a high-speed mixer for stirring. After being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a 5VA high flame retardant ABS resin composition; the twin-screw extruder has a screw aspect ratio of 30 to 50, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200° C. to 240° C., and the screw speed is 300 rpm to 500 rpm.
[0037] The raw materials and equipment used in the present invention are all conventional raw materials and equipment in the art. In the following embodiments, raw materials or processing techniques, unless otherwise specified, are all conventional commercially available raw materials or conventional processing techniques in the art.
[0038] For example, the antioxidant Irganox 1010, Irganox 1076, Irganox B900 or Irganox 168 used in the present invention are purchased from CIBA Fine Chemical Company; ABS-1 resin is PA747, purchased from CHIMEI Company; ABS-2 resin is ABS8391, purchased from Shanghai Gaoqiao Petrochemical Company; chlorinated polyethylene is CPE135A, purchased from Weifang Yaxing Chemical Co., Ltd.; bromotriazine FR245, whose bromine content is 67%, purchased from Shandong Shouguang Weidong Chemical Co., Ltd.; 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, purchased from Lanxess; nano-montmorillonite MMT was purchased from Beijing Qinglian Kenami Plastic Co., Ltd.; styrene-maleic anhydride copolymer SMA700, with a molecular weight of 120,000-180,000 and a maleic anhydride (MAH) content of 18wt%, was purchased from Jiaxing Huawen Chemical Co., Ltd.; styrene-maleic anhydride copolymer SMA150, with a maleic anhydride (MAH) content of 50wt% and a molecular weight of 5000, was purchased from Jiaxing Huawen Chemical Co., Ltd.; antimony trioxide was purchased from Hunan Shanxing Antimony Industry; light stabilizer UVP and hindered amine light stabilizer 770 were purchased from CIBA Fine Chemical Company; the anti-dripping agent is PTFE SN3300B7, purchased from Guangzhou Entropy Innovation Materials Co., Ltd.
[0039] Example 1
[0040] This embodiment provides a 5VA high flame retardant ABS resin composition, which comprises the following components by weight:
[0041]
[0042] The nano carbon-forming masterbatch A in this embodiment is a nano montmorillonite masterbatch, which comprises the following components by weight:
[0043]
[0044] The preparation method of the nano-carbon masterbatch A of the present embodiment comprises the following steps: ABS-2 resin ABS8391, nano-montmorillonite MMT, SMA150 and processing aids (Irganox 1076, Irganox 168 and EBS) are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain the nano-carbon masterbatch A; the twin-screw extruder has a screw aspect ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm.
[0045] The 5VA highly flame-retardant ABS resin composition of this embodiment is prepared by the following method:
[0046] ABS resin PA747, chlorinated polyethylene CPE135A, 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, antimony trioxide, nano carbon masterbatch A, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a 5VA high flame retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200°C to 240°C, and the screw speed is 400 rpm.
[0047] Example 2
[0048] This embodiment provides a 5VA high flame retardant ABS resin composition, which comprises the following components by weight:
[0049]
[0050] The nano carbon-forming masterbatch A in this embodiment is a nano montmorillonite masterbatch, which comprises the following components by weight:
[0051]
[0052] The preparation method of the nano-carbon masterbatch A of the present embodiment comprises the following steps: ABS-2 resin ABS8391, nano-montmorillonite MMT, SMA150 and processing aids (Irganox 1076, Irganox 168 and EBS) are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain the nano-carbon masterbatch A; the twin-screw extruder has a screw aspect ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm.
[0053] The 5VA highly flame-retardant ABS resin composition of this embodiment is prepared by the following method:
[0054] ABS resin PA747, chlorinated polyethylene CPE135A, 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, antimony trioxide, nano carbon masterbatch A, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a 5VA high flame retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200°C to 240°C, and the screw speed is 400 rpm.
[0055] Example 3
[0056] This embodiment provides a 5VA high flame retardant ABS resin composition, which comprises the following components by weight:
[0057]
[0058] The nano carbon-forming masterbatch A in this embodiment is a nano montmorillonite masterbatch, which comprises the following components by weight:
[0059]
[0060]
[0061] The preparation method of the nano-carbon masterbatch A of the present embodiment comprises the following steps: ABS-2 resin ABS8391, nano-montmorillonite MMT, SMA150 and processing aids (Irganox 1076, Irganox 168 and EBS) are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain the nano-carbon masterbatch A; the twin-screw extruder has a screw aspect ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm.
[0062] The 5VA highly flame-retardant ABS resin composition of this embodiment is prepared by the following method:
[0063] ABS resin PA747, chlorinated polyethylene CPE135A, 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, antimony trioxide, nano carbon masterbatch A, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a 5VA high flame retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200°C to 240°C, and the screw speed is 400 rpm.
[0064] Example 4
[0065] This embodiment provides a 5VA high flame retardant ABS resin composition, which comprises the following components by weight:
[0066]
[0067] The nano carbon-forming masterbatch A in this embodiment is a nano montmorillonite masterbatch, which comprises the following components by weight:
[0068]
[0069] The preparation method of the nano-carbon masterbatch A of the present embodiment comprises the following steps: ABS-2 resin ABS8391, nano-montmorillonite MMT, SMA150 and processing aids (Irganox 1076, Irganox 168 and EBS) are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain the nano-carbon masterbatch A; the twin-screw extruder has a screw aspect ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm.
[0070] The 5VA highly flame-retardant ABS resin composition of this embodiment is prepared by the following method:
[0071] ABS resin PA747, chlorinated polyethylene CPE135A, 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, antimony trioxide, nano carbon masterbatch A, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a 5VA high flame retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200°C to 240°C, and the screw speed is 400 rpm.
[0072] Example 5
[0073] This embodiment provides a 5VA high flame retardant ABS resin composition, which comprises the following components by weight:
[0074]
[0075]
[0076] The nano carbon-forming masterbatch A in this embodiment is a nano montmorillonite masterbatch, which comprises the following components by weight:
[0077]
[0078] The preparation method of the nano-carbon masterbatch A of the present embodiment comprises the following steps: ABS-2 resin ABS8391, nano-montmorillonite MMT, SMA150 and processing aids (Irganox 1076, Irganox 168 and EBS) are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain the nano-carbon masterbatch A; the twin-screw extruder has a screw aspect ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm.
[0079] The 5VA highly flame-retardant ABS resin composition of this embodiment is prepared by the following method:
[0080] ABS resin PA747, chlorinated polyethylene CPE135A, 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, antimony trioxide, nano carbon masterbatch A, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a 5VA high flame retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200°C to 240°C, and the screw speed is 400 rpm.
[0081] Comparative Example 1
[0082] This comparative example provides an ABS resin composition, which comprises the following components by weight:
[0083]
[0084]
[0085] The ABS resin composition of this comparative example was prepared by the following method:
[0086] ABS resin PA747, chlorinated polyethylene CPE135A, bromotriazine FR245, antimony trioxide, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent to a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain an ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200° C. to 240° C., and the screw speed is 400 rpm.
[0087] Comparative Example 2
[0088] This comparative example provides a flame retardant ABS resin composition, which comprises the following components by weight:
[0089]
[0090] The flame retardant ABS resin composition of this comparative example is prepared by the following method:
[0091] ABS resin PA747, chlorinated polyethylene CPE135A, bromotriazine FR245, antimony trioxide, nano-montmorillonite MMT, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent to a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a flame-retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200° C. to 240° C., and the screw speed is 400 rpm.
[0092] Comparative Example 3
[0093] This comparative example provides a flame retardant ABS resin composition, which comprises the following components by weight:
[0094]
[0095] The nano carbon masterbatch B in this comparative example is a nano montmorillonite masterbatch, which comprises the following components by weight:
[0096]
[0097] The preparation method of the nano-carbon-forming masterbatch B of this comparative example comprises the following steps: ABS-2 resin ABS8391, nano-montmorillonite MMT, SMA700 and processing aids (Irganox 1076, Irganox 168 and EBS) are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device, and under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain the nano-carbon-forming masterbatch B; the twin-screw extruder has a screw aspect ratio of 40, and is equipped with a temperature control device and a vacuum device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm.
[0098] The flame retardant ABS resin composition of this comparative example is prepared by the following method:
[0099] ABS resin PA747, chlorinated polyethylene CPE135A, 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, antimony trioxide, nano carbon masterbatch B, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a flame-retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200°C to 240°C, and the screw speed is 400 rpm.
[0100] Comparative Example 4
[0101] This comparative example provides a flame retardant ABS resin composition, which comprises the following components by weight:
[0102]
[0103] The nano carbon-forming masterbatch A in this comparative example is a nano montmorillonite masterbatch, which comprises the following components by weight:
[0104]
[0105] The preparation method of the nano-carbon-forming masterbatch A of the comparative example comprises the following steps: feeding ABS-2 resin ABS8391, nano-montmorillonite MMT, SMA150 and processing aids (Irganox 1076, Irganox 168 and EBS) into a high-speed mixer for stirring, stirring and fully mixing in the high-speed mixer, and then feeding into a twin-screw extruder through a metering device, and under the conveying, shearing and mixing of the screw, the material is melted, homogenized, drawn, cooled and pelletized to obtain the nano-carbon-forming masterbatch A; the twin-screw extruder has a screw aspect ratio of 40, and is equipped with a temperature control device and a vacuum device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm.
[0106] The flame retardant ABS resin composition of this comparative example is prepared by the following method:
[0107] ABS resin PA747, chlorinated polyethylene CPE135A, 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, antimony trioxide, nano carbon masterbatch A, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a flame-retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200° C. to 240° C., and the screw speed is 400 rpm.
[0108] Comparative Example 5
[0109] This comparative example provides a flame retardant ABS resin composition, which comprises the following components by weight:
[0110]
[0111] The nano carbon-forming masterbatch A in this comparative example is a nano montmorillonite masterbatch, which comprises the following components by weight:
[0112]
[0113] The preparation method of the nano-carbon-forming masterbatch A of the comparative example comprises the following steps: feeding ABS-2 resin ABS8391, nano-montmorillonite MMT, SMA150 and processing aids (Irganox 1076, Irganox 168 and EBS) into a high-speed mixer for stirring, stirring and fully mixing in the high-speed mixer, and then feeding into a twin-screw extruder through a metering device, and under the conveying, shearing and mixing of the screw, the material is melted, homogenized, drawn, cooled and pelletized to obtain the nano-carbon-forming masterbatch A; the twin-screw extruder has a screw aspect ratio of 40, and is equipped with a temperature control device and a vacuum device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm.
[0114] The flame retardant ABS resin composition of this comparative example is prepared by the following method:
[0115] ABS resin PA747, chlorinated polyethylene CPE135A, bromotriazine FR245, antimony trioxide, nano carbon masterbatch A, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent to a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a flame-retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200° C. to 240° C., and the screw speed is 400 rpm.
[0116] Comparative Example 6
[0117] This comparative example provides a flame retardant ABS resin composition, which comprises the following components by weight:
[0118]
[0119] The flame retardant ABS resin composition of this comparative example is prepared by the following method:
[0120] ABS resin PA747, chlorinated polyethylene CPE135A, 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, antimony trioxide, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a flame-retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200° C. to 240° C., and the screw speed is 400 rpm.
[0121] Comparative Example 7
[0122] This comparative example provides a 5VA high flame retardant ABS resin composition, which comprises the following components by weight:
[0123]
[0124] The nano carbon-forming masterbatch A in this comparative example is a nano montmorillonite masterbatch, which comprises the following components by weight:
[0125]
[0126] The preparation method of the nano-carbon-forming masterbatch A of the comparative example comprises the following steps: feeding ABS-2 resin ABS8391, nano-montmorillonite MMT, SMA150 and processing aids (Irganox 1076, Irganox 168 and EBS) into a high-speed mixer for stirring, stirring and fully mixing in the high-speed mixer, and then feeding into a twin-screw extruder through a metering device, and under the conveying, shearing and mixing of the screw, the material is melted, homogenized, drawn, cooled and pelletized to obtain the nano-carbon-forming masterbatch A; the twin-screw extruder has a screw aspect ratio of 40, and is equipped with a temperature control device and a vacuum device, the extrusion temperature is 190°C to 230°C, and the screw speed is 300 rpm.
[0127] The 5VA highly flame-retardant ABS resin composition of this embodiment is prepared by the following method:
[0128] ABS resin PA747, chlorinated polyethylene CPE135A, 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer BC58, antimony trioxide, nano carbon masterbatch A, anti-dripping agent PTFE SN3300B7, antioxidant Irganox B900, light stabilizer UVP, hindered amine light stabilizer 770 and lubricant EBS are sent into a high-speed mixer for stirring, and after being stirred and fully mixed in the high-speed mixer, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a 5VA high flame retardant ABS resin composition; the twin-screw extruder has a screw length-diameter ratio of 40, and is equipped with a temperature control device and a vacuum pumping device, the extrusion temperature is 200°C to 240°C, and the screw speed is 400 rpm.
[0129] Performance test (tensile strength, melt index, impact strength, flame retardancy)
[0130] The performance tests of the above Examples 1-5 and Comparative Examples 1-7 are as follows:
[0131] The tensile strength test was carried out according to ASTM D638 standard, and the test speed was 50 mm / min.
[0132] The melt index test was carried out according to ASTM D1238 standard, with a load of 10 kg and a test temperature of 220°C.
[0133] The notched impact strength test was carried out according to ASTM D256.
[0134] The flame retardant test is carried out according to UL94 standard.
[0135] The components, contents (by weight) and properties of the above-mentioned Examples 1-5 and Comparative Examples 1-7 are shown in Table 1.
[0136] Table 1 Components, contents (weight) and properties in Examples 1-5 and Comparative Examples 1-7
[0137]
[0138]
[0139] It can be seen from Examples 1-5 and Comparative Example 6 in Table 1 that the present invention can significantly improve the 5VA flame retardant performance under the synergistic carbonization effect of the aromatic brominated flame retardant and the nano carbon-forming masterbatch, and can pass the 5VA flame retardant grade of 2.0 mm thickness;
[0140] From Table 1, Comparative Example 1, it can be seen that the traditional bromine-antimony flame-retardant ABS system is difficult to pass the 5VA flame-retardant grade;
[0141] From Table 1, it can be seen that when the amount of nano-montmorillonite MMT added is high, the traditional bromine-antimony flame-retardant ABS system cannot pass the 2.0 mm 5VA flame-retardant test, but instead sharply deteriorates the impact performance of the flame-retardant ABS.
[0142] It can be seen from Example 2 and Comparative Example 3 in Table 1 that the dispersion and flaking of nano-montmorillonite in the nano-carbon-forming masterbatch are also particularly important. When conventional SMA700 (molecular weight of 120,000-180,000) is used as a dispersant, due to its molecular weight higher than 20,000, the surface wetting is poor, and the nano-montmorillonite flaking and dispersion cannot be effectively improved, which ultimately affects the flame retardant effect and cannot pass the 2.0mm 5VA flame retardant test. Therefore, the flame retardant improvement effect embodied by the nano-carbon-forming masterbatch-B is not as good as that of the nano-carbon-forming masterbatch-A.
[0143] It can be seen from Comparative Examples 4 and 5 in Table 1 that when the content of the nano-carbon-forming masterbatch is less than 3 parts (Comparative Example 4), or when the nano-carbon-forming masterbatch is compounded with the traditional flame retardant bromotriazine (Comparative Example 5), good 5VA flame retardant performance cannot be achieved. Therefore, the present invention utilizes the synergistic carbonizing effect between the nano-carbon-forming masterbatch with a weight portion of not less than 3 parts and the aromatic brominated flame retardant to significantly improve the 5VA flame retardant performance of ABS resin.
[0144] It can be seen from Comparative Example 7 in Table 1 that when the addition amount of nano-carbon-forming masterbatch is too high, although the ABS resin has excellent 5VA high flame retardancy, its impact performance is greatly affected. Therefore, the present invention utilizes nano-carbon-forming masterbatch with a weight portion not exceeding 6 to participate in synergistic carbonization, thereby greatly improving the flame retardant efficiency while improving the physical properties of the ABS resin, thereby achieving a dual improvement in the flame retardant properties and physical properties of the ABS resin.
[0145] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A 5VA highly flame-retardant ABS resin composition, characterized in that: By weight, it includes the following components:
2. A 5VA highly flame-retardant ABS resin composition according to claim 1, characterized in that: The ABS resin is selected from any one of acrylonitrile-butadiene-styrene copolymer, acrylonitrile-butadiene-acrylate copolymer, methyl methacrylate-butadiene-styrene copolymer or acrylonitrile-ethylene propylene diene monomer rubber-styrene copolymer.
3. A 5VA highly flame-retardant ABS resin composition according to claim 1, characterized in that: The chlorine content of the chlorinated polyethylene is 32% to 35%.
4. A 5VA highly flame-retardant ABS resin composition according to claim 1, characterized in that: The aromatic brominated flame retardant is selected from at least one of 2,4,6-tribromophenoxy-terminated tetrabromobisphenol-A carbonate oligomer, decabromodiphenylethane, brominated epoxy resin or brominated polystyrene.
5. A 5VA highly flame-retardant ABS resin composition according to claim 1, characterized in that: The antimony-based flame retardant synergist is selected from any one of antimony trioxide, antimony pentoxide or sodium antimonate.
6. A 5VA highly flame-retardant ABS resin composition according to claim 1, characterized in that: The nano carbon-forming masterbatch is a nano montmorillonite masterbatch, which comprises the following components by weight: 40-50 parts of acrylonitrile-butadiene-styrene copolymer, 45-60 parts of nano montmorillonite, 3-5 parts of surfactant and 0.5-1 part of processing aid.
7. A 5VA highly flame-retardant ABS resin composition according to claim 6, characterized in that: The surfactant is a styrene-maleic anhydride copolymer, the molecular weight of which is 5000-20000, and the content of maleic anhydride is 18wt%-25wt%; The processing aid is selected from at least one of hindered phenol antioxidants, phosphite antioxidants, thioester antioxidants, polyethylene wax, oxidized polyethylene wax, ethylene bisstearamide, pentaerythritol stearate, erucamide, silicone oil, magnesium stearate, and calcium stearate lubricants.
8. A 5VA highly flame-retardant ABS resin composition according to claim 6, characterized in that: The preparation method of the nano carbon masterbatch comprises the following steps: The acrylonitrile-butadiene-styrene copolymer, nano-montmorillonite, surfactant and processing aid are mixed and stirred, and after being uniformly stirred, they are sent into a twin-screw extruder through a metering device. Under the conveying, shearing and kneading of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain nano-carbon masterbatch; The screw length-to-diameter ratio of the twin-screw extruder is 30-50, the extrusion temperature is 190° C.-230° C., and the screw speed is 300-500 rpm.
9. A 5VA highly flame-retardant ABS resin composition according to claim 1, characterized in that: The anti-dripping agent is selected from polytetrafluoroethylene with a molecular weight of 3 million to 5 million, Any one of AD high-performance silicon-coated anti-drip agent, Flyho K-PT201 or Flyho K-PT107; the antioxidant is selected from at least one of Irganox 1010, Irganox1076, Irganox B900 or Irganox 168; the light stabilizer is selected from at least one of 1-hydroxybenzotriazole, 2-hydroxybenzophenone, UVP, hindered amine light stabilizer 770 or salicylate; the lubricant is selected from at least one of ethylene bisstearamide, white oil, fatty acid amide, barium stearate, magnesium stearate, polyethylene wax, silicone oil, ethylene-vinyl acetate copolymer or ethylene-acrylic acid copolymer.
10. A method for preparing a 5VA highly flame-retardant ABS resin composition according to any one of claims 1 to 9, characterized in that: The steps include: ABS resin, chlorinated polyethylene, aromatic brominated flame retardant, antimony flame retardant synergist, nano carbon masterbatch, anti-dripping agent, antioxidant, light stabilizer and lubricant are mixed and stirred, and after being uniformly stirred, the mixture is sent into a twin-screw extruder through a metering device. Under the conveying, shearing and kneading of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a 5VA high flame retardant ABS resin composition; The screw length-diameter ratio of the twin-screw extruder is 30-50, the extrusion temperature is 200° C.-240° C., and the screw speed is 300-500 rpm.
Citation Information
Patent Citations
Low-L value inflaming retarding ABS modified resin and preparation method thereof
CN101787174B
An ABS composite material
CN109627671B
Cited By
Flame-retardant ABS composite material and preparation method thereof
CN120590745A
A flame-retardant ABS composite material and its preparation method
CN120590745B